1997
DOI: 10.1146/annurev.biochem.66.1.173
|View full text |Cite
|
Sign up to set email alerts
|

POLYADENYLATION OF mRNA IN PROKARYOTES

Abstract: The 3'-ends of both prokaryotic and eukaryotic mRNA are polyadenylated, but the poly(A) tracts of prokaryotic mRNA are generally shorter, ranging from 15 to 60 adenylate residues and associated with only 2-60% of the molecules of a given mRNA species. The sites of polyadenylation of bacterial mRNA are diverse and include the 3'-ends of primary transcripts, the sites of endonucleolytic processing in the 3' untranslated and intercistronic regions, and sites within the coding regions of mRNA degradation products.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
0
9

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(182 citation statements)
references
References 105 publications
3
170
0
9
Order By: Relevance
“…Using swap experiments between CCA-adding enzymes and the N and C termini of the class II Escherichia coli poly(A) polymerase (23,24), Betat et al (25) identified a region between residues 219 and 245 in the CCA-adding enzyme that determined whether the chimeric enzymes behaved as a CCA-adding enzyme or a poly(A) polymerase. The ability of this region to confer CCA-adding activity on the N terminus of poly(A) polymerase is most surprising and is consistent with the notion that scrunching, counting, and the nucleotide specificity switch in class II CCA-adding enzymes may be localized, intrinsic characteristics of the NTR active site; however, we hesitate to interpret the results of Betat et al (25) structurally because no structure has been determined for E. coli poly(A) polymerase; the helix M regions of the E. coli poly(A) polymerase and CCA-adding enzymes exhibit little if any homology; and helix M appears to be remote from the tRNA acceptor stem in the cocrystal structure of the A. aeolicus A-adding enzyme (21).…”
Section: Resultsmentioning
confidence: 99%
“…Using swap experiments between CCA-adding enzymes and the N and C termini of the class II Escherichia coli poly(A) polymerase (23,24), Betat et al (25) identified a region between residues 219 and 245 in the CCA-adding enzyme that determined whether the chimeric enzymes behaved as a CCA-adding enzyme or a poly(A) polymerase. The ability of this region to confer CCA-adding activity on the N terminus of poly(A) polymerase is most surprising and is consistent with the notion that scrunching, counting, and the nucleotide specificity switch in class II CCA-adding enzymes may be localized, intrinsic characteristics of the NTR active site; however, we hesitate to interpret the results of Betat et al (25) structurally because no structure has been determined for E. coli poly(A) polymerase; the helix M regions of the E. coli poly(A) polymerase and CCA-adding enzymes exhibit little if any homology; and helix M appears to be remote from the tRNA acceptor stem in the cocrystal structure of the A. aeolicus A-adding enzyme (21).…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, polyadenylation of mRNAs, which is primarily carried out by E. coli Poly(A) polymerase (PAP I), instead seems to have a role in the degradation of mRNA (31). Some years ago, it was noticed that the degradation of mRNA or mRNA fragments by exonucleases is reduced when PAP I is absent in the cell (32,33).…”
Section: Cofactors In Rna Degradationmentioning
confidence: 99%
“…Polyadenylation of the 39-ends of RNAs, once thought to occur exclusively in eukaryotic cells, has now been shown definitively to occur in bacterial systems as well (Carpousis et al, 1999;Rauhut & Klug, 1999;Sarkar, 1996Sarkar, , 1997. In Escherichia coli, polyadenylation targets RNAs for degradation (Carpousis et al, 1999;Régnier & Arraiano, 2000).…”
Section: Introductionmentioning
confidence: 99%